The Political Context of Judicial Review in Indonesia - Siregar, Fritz Edward (UI Scholars Hub, 2015)
The Constitutional Court of Indonesia plays significant role in securing democracy in Indonesia. In exercising their authorities, including the election result dispute and judicial review, the Court continues to affirm institutional judicial legitimacy and pursue their role to guard 1945 Constitution. The first Chief Justice Jimly Asshiddiqie showed how within five years of the Court’s establishment, he could strategically maximize its momentum and build the Court as a respectful institution. The Chief Justice Mahfud M D was then elected to reduce the judicial activism started by Jimly’s bench. However, against promises and expectations, Mahfud M D brought the Court to a level far beyond the imagination of the Constitution drafters. Parliament and President tried to limit the Court’s authority, not ones, and the Court was able to overcome those constrain. Current various available studies observed only how the Court issued their decisions and solely focus to the impact of the decisions. Scholars slightly ignore other constitutional actors in studying about the Court. In fact, political environment where the Court operated is one of the most important aspects which strengthen the Court’s institutional legitimacy. This paper attempts to discover the rise of the Court from political environment view outside the court. Political parties’ maturity and political constraint are the key factors that support the development of the Court’s institutional power.